Controversial Issues and their Impact on the Construction and Reshaping of EFL Learners' Habitus - Ortiz López, Juan Eduardo; Keitt, Tracey (Colombian Applied Linguistics Journal, 2022)
The following study aims to explore Bourdieu’s notion of habitus and its shaping and re-shaping through exposure of authentic oral input. The study used podcasts as an EFL teaching strategy where learners were expected to confront their dispositions. For the purpose of this study, the mental illness issue was employed as a controversial topic. The research used a grounded theory approach and multi-case study design where three unstructured interviews were implemented in each case along the teaching process. Content analysis was applied and research generated categories emerged from the coding process. The results reveal that the EFL learning process has the potential to become a subversive form of defying culturally dominant dispositions and to enhance the learners’ probabilities of re-shaping habitus as well as learning a foreign language. According to the findings of this study, the inclusion of authentic controversial podcasts as listening comprehension tasks, which challenge EFL students’ habitus, can become a successful strategy to modify their cultural dispositions along with learning English as a foreign language.